Multiplication Training Using Fingers to Support Mathematics Learning for Students of Grades VIII and IX at PPWNI Klang - Afifah Hilmia Nugroho; Anna Nabila Faradita; Farah Lafas Syahdana; Latutik Mukhlisin (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
The observation conducted during the Community Service Program (KKN) at PPWNI Klang from January 30, 2023, to February 10, 2023, yielded the result that nearly 80% of students in grades VIII and IX did not have a strong understanding of the concept of multiplication. Multiplication is one of the fundamental arithmetic operations that is highly important in mathematics education. Therefore, it is necessary to provide training on how to multiply using fingers as a tool to support mathematics learning for students in grades VIII and IX at SMP PPWNI Klang. This community service activity has the potential to broaden students' knowledge and skills in solving mathematical problems. This was evident during the learning sessions when many students showed enthusiasm, helped each other, and engaged in discussions while solving problems that involved multiplication concepts.